2018
DOI: 10.5194/soil-2017-41
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty indication in soil function maps – Transparent and easy-to-use information to support sustainable use of soil resources

Abstract: Abstract. The mapping of soil functions is increasingly being used to inform decision-making in spatial planning processes related to the capacity of soils to contribute to ecosystem services. In this study, we add to the transparency of soil function maps by indicating uncertainties arising from prediction uncertainties of soil properties as generated by digital soil mapping (DSM). For a study area in the Swiss Midlands, we map 10 static soil functions for agricultural soils together with their uncertainties,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…More details regarding the SEPP tool and the assessed soil functions are provided in the SEPP user manual (Supporting Information) and by Gruber et al (2019), who applied the tool. However, an updated version of the SEPP tool – in comparison to the version used by Gruber et al (2019) – was used in this study, where the ordinal scale was inverted to match the logic of SFAs in Germany, Austria and Switzerland (see BayGLA and BayLfU, 2003; Greiner et al, 2018; Haslmayr et al, 2016), with 1 representing a low and 5 representing a high level of function fulfilment. The underlying, sometimes slightly modified, methods were originally developed in Germany and published by Ad‐hoc‐AG Boden (2000), BayGLA and BayLfU (2003), BVB (2005), Gerstenberg and Smettan (2005), Lehmann et al (2008), Müller and Waldeck (2011), and Umweltministerium Baden‐Württemberg (1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More details regarding the SEPP tool and the assessed soil functions are provided in the SEPP user manual (Supporting Information) and by Gruber et al (2019), who applied the tool. However, an updated version of the SEPP tool – in comparison to the version used by Gruber et al (2019) – was used in this study, where the ordinal scale was inverted to match the logic of SFAs in Germany, Austria and Switzerland (see BayGLA and BayLfU, 2003; Greiner et al, 2018; Haslmayr et al, 2016), with 1 representing a low and 5 representing a high level of function fulfilment. The underlying, sometimes slightly modified, methods were originally developed in Germany and published by Ad‐hoc‐AG Boden (2000), BayGLA and BayLfU (2003), BVB (2005), Gerstenberg and Smettan (2005), Lehmann et al (2008), Müller and Waldeck (2011), and Umweltministerium Baden‐Württemberg (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there are various SFA methods that depend on the soil function to be assessed and the availability of soil data. The evaluation is usually performed using empirical equations, pedotransfer functions, lookup tables, or a combination thereof (Greiner et al, 2018). The procedure can be time‐consuming and error‐prone, particularly if several soil functions and/or more than a handful of sites are considered.…”
Section: Introductionmentioning
confidence: 99%
“…the vagueness of concepts such as a 'deep soil', which play a part in data interpretation) (Li et al 2018). For this reason it is widely recognized in geographical information science (GIScience) that the uncertainty about spatial information must be communicated to its end-users if they are to apply it effectively (Li et al 2012, Greiner et al 2018. Heuvelink and Burrough (2002) suggested that it is necessary to address how stakeholders deal with problems of uncertainty in spatial information as part of a decision making process.…”
Section: The General Contextmentioning
confidence: 99%
“…Other approaches have been used to compute local probabilites that variables exceed thresholds of environmental significance. These include copulas, conditional simulation and Bayesian methods to compute or sample from a local posterior distribution (Goovaerts 2001, Marchant et al 2011, Greiner et al 2018.…”
Section: The General Contextmentioning
confidence: 99%